The mechanism of recrystallization of carbon steels - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия)
A nanostructural mechanism for recrystallization of carbon steels has been developed. First, structure‑forming nanocrystals of austenite, ferrite and cementite are formed from elementary nanocrystals of iron and graphite, free iron and carbon atoms. The crystallization centers of microcrystals of phases are formed from them. From these centers, structure‑forming nanocrystals of phases, free iron and carbon atoms, microcrystals of austenite, ferrite and cementite of carbon steels are formed.